Evolution of multiple, mutually orthogonal prolyl-tRNA synthetase/tRNA pairs for unnatural amino acid mutagenesis in Escherichia coli - Chatterjee, Abhishek; Xiao, Han; Schultz, Peter G (Proceedings of the National Academy of Sciences - PNAS, 2012)
The site-specific incorporation of unnatural amino acids (UAAs) into proteins in living cells relies on an engineered tRNA/aminoacyl-tRNA synthetase (tRNA/aaRS) pair, orthogonal to the host cell, to deliver the UAA of choice in response to a unique nonsense or frameshift codon. Here we report the generation of mutually orthogonal prolyl-tRNA/prolyl-tRNA synthase (ProRS) pairs derived from an archaebacterial ancestor for use in Escherichia coli. By reprogramming the anticodon-binding pocket of Pyrococcus horikoshii ProRS (PhProRS), we were able to identify synthetase variants that recognize engineered Archaeoglobus fulgidus prolyl-tRNAs (Af-tRNA(Pro)) with three different anticodons: CUA, AGGG, and CUAG. Several of these evolved PhProRSs show specificity toward a particular anticodon variant of Af-tRNA(Pro), whereas others are promiscuous. Further evolution of the Af-tRNA(Pro) led to a variant exhibiting significantly improved amber suppression efficiency. Availability of a prolyl-tRNA/aaRS pair should enable site-specific incorporation of proline analogs and other N-modified UAAs into proteins in E. coli. The evolution of mutually orthogonal prolyl-tRNA/ProRS pairs demonstrates the plasticity of the tRNA-aaRS interface and should facilitate the incorporation of multiple, distinct UAAs into proteins.